The origami revolution [videorecording (DVD)] - Effros, Jamie (PBS Distribution, 2017)
Origami, the century old tradition of paper folding is now at the heart of a scientific revolution. Scientists are discovering that folding is a powerful tool to explore the limits of science. Engineers and designers are now adopting origami designs to conquer space or reshape the world around us. From aircraft design to protein folding to micro-robots, join NOVA to discover how the age-old art of origami is transforming our world.